Hubungan Peringatan Kesehatan Bergambar Di Bungkus Rokok dengan Praktik Merokok Perokok Pemula pada SMP X di Kota Semarang - Ririn Wulansari; VG Tinuk Istiarti; Kusyogo Cahyo (Jurnal Kesehatan Masyarakat (Undip), 2016)
Some studies from the International Tobacco Control showed that, the implementation of pictorial health warnings have an impact on smoker to quit smoking. In Indonesia, there is Regulation of Health Minister No. 28/2013 about Implementation of Health Warnings and Health Information on Tobacco Product, which regulate the implementation of pictorial health warnings on tobacco produck. The purpose of this research is to analyze the relationship of pictorial health warning wrap cigarette on the smoking new smokers in SMP X Semarang City. Type of this research is analitycal descriptive with quantitative approach. The population are students in grade 7th and 8th who have characteristics as new smoker and willing to become respondens.The whole question has been tested for validity and reliability. Analysis of data using statistical analysis of Chi Square test (significance level 0.05). The results showed that, most of the respondents were 13-15 years of age, and the grade level of the respondents were in grade 7 and most of respondens including category pocket money low (<Rp 10.000).The variables associated with new smoker smoking behavior, which are :pictorial health warnings on cigarette packs (p= 0.000), reached with pictorial health warning (p=0,021), and peer support (p = 0.009). While variables age (p= 1), pocket money (p=0,438), the grade lavel of respondens (p = 0,223), knowledge about pictorial health warning (p=0.714), the attitude with pictorial health warning (p= 1,000),  teacher’s support (p=0,662) not associated with new smoker smoking behavior. On this research, writter suggests the goverment who concern on healthy should implement of pictorial health warnings more focusing on the picture and information on cigarette packs.